Motives and relevance of online friendships - Damaschke, K.; Kommers, Piet (Inderscience Publishers, 2012)
A short interview-based study looks at the different motives why persons establish online friendships, for example via Facebook. Further reasons are discovered during a second study - an online focus group. This study also looked into the differences in importance that profile owners attach to different (groups of) online friends. The results of Study 2 were analysed using qualitative content analysis and resulted in the formation of four categories of factors influencing the number of friendships a person establishes online; namely 1 person-focused 2 online-friends 3 purpose 4 dedication. These categories serve as a tool for employers, helping them to assess an applicant based on his/her number of online friends. The categories allow for a rationalisation of the conclusions made. Despite the considerable insights into the driving forces for the establishment of online friendships gained, there certainly is room for future research to further refine the presented categories.